A novel method for chatter control and improvement of surface finish in end milling - Amin, A. K. M. Nurul; Sulaiman, Syidatul Akma (2012)
Machining of metals is generally accompanied by a violent relative vibration between work and tool, known as chatter. Chatter arises due to resonance when the frequency of instability of chip formation and the natural frequencies (vibration modes) of the machine-system components coincide. Chatter has detrimental effects on tool life, productivity, the topology and dimensional accuracy of the work-piece apart from its other harmful effects. Finishing and grinding operations are usually required in order to improve the quality of the finished products in End milling of alloys such as Ti-6Al-4V in the absence of any chatter control strategy. The researchers of this work have developed a novel technique to address this issue in end milling operation. The setup consisted of a specially designed fixture, to be mounted on a Vertical milling machine or a Machining Center spindle, to locate and clamp two permanet ferrite magnet bars (dimensions: 1″x6″x3″) located at either side of the cutting tool and maintaining a suitable distance (approximately 5mm) from the tool. The fixture is designed to provide uniform magnetic field by the two magnets of strength 2500-2700 Gauss. The fixture design can be adjusted to suit any spindle diameter and the method can be applied to any vertical milling machine or machining center. The advantage of the new method is illustrated in the example of a end milled of a Ti alloy - Ti6Al4V block. The design of the experiments conducted was done using the statistical method - Response Surface Methodology (RSM) utilizing the capabilities of the Design Expert Software. Three variable parameters cutting speed, feed and depth of cut with three levels of these parameters and two response parameters – vibration/chatter amplitude and average surface roughness were considered in this design. Two sets of experiments, with and without magnets application, were conducted adopting the above RSM design of experiments. For vibration monitoring and analysis, a (16 channel rack) DAQ card and Datalog DASY Lab 5.6, with built-in Fast Fourier Transform (FFT), were used and Mitutoyo SURFTEST SV-500 was used to measure the resultant surface roughness. Apart from that the effect of magne appliation on chip serration instability was studied using Scanning Electron Microscope (SEM). It is observed that cutting the presence of magnets leads to an average reductions in vibration amplitude by 20% and surface roughness by 40%. The SEM analysis demonstated that chip formations were more stable while cutting under the presence of permanent magnets. Finally, the reduction in surface roughness eliminated the need for subsequent grinding and polishing. The cost of the fixture and the magnets are low and the method can be applied to any vertical milling operation and can also be adapted to other cutting process. It is a harmless and green technique for improved machinability of materials, both metallic as well as non metallic.